Shanghai-Hong Kong stock connect: an analysis of Chinese partial stock market liberalization impact on the local and foreign markets - Bai, Ye; Yan Pang Chow, Darien (Elsevier, 2017)
Shanghai-Hong Kong Stock Connect is a partial liberalization providing domestic and foreign investors mutual access to stock markets. This study analyzes post-liberalization short- and medium-term impacts on both local and foreign markets. Our results suggest that contrasting to the expectation of homogeneous mutual benefits, the implementation of the Connect have asymmetric impacts on mainland and Hong Kong stock markets. They are driven by the unbalanced developments of both markets. In the medium-term, we find increasing market liquidity and size but also increasing risk persistence and exposure to systematic risk, though the magnitude of changes vary between two markets.